Science lesson plan evaluation for 7th grade secondary school: A learning process reflection - Fithriyyati, Nilia; Maryani, Ika (Research and Social Study Institute, 2018)
The study aimed to determine the suitability of the Lesson Plan for 7th grade Secondary School with the Learning Process Standard based on the aspects of planning, implementation, and assessment. The particular research was an evaluation research with the CIPP model (Context, Input, Process, and Product). The lesson plan documents were from five schools implementing the Curriculum 2006 and five schools implementing the Curriculum 2013. The respondents were 10 science teachers of 7th grade and 472 students. Data collection instruments were observation guides, questionnaires, interview guides, and documentation. Data analysis techniques were quantitative and qualitative. The Quantitative data was T-score; meanwhile, qualitative data analyzed descriptively. Lesson Plans with the rules of the Curriculum 2006 and Curriculum 2013 were the main documents in the evaluation. The results showed that (1) the suitability of the science lesson plan using KTSP (curriculum 2006) was in category of adequate suitable and lesson plan using K-13 (curriculum 2013) was in suitable category; (2) the suitability of the implementation of science learning using KTSP and K-13 was in category of adequate suitable; and (3) the suitability of the assessment of science learning using KTSP and K-13 was in category of adequate suitable. Generally, the documents of the science lesson plan were adequate suitable with the Learning Process Standards.